ANALYSIS OF HEALTH SERVICES MAXIMUM SUPPLY IN HOSPITAL SURABAYA - Novia Dewi Putri Ayuningtyas (Journal of Public Health Research and Community Health Development, 2019)
The importance of a health service  in calculating the maximum supply is to ensure efficiency and effectiveness. To achieve efficiency and effectiveness it is important to pay attention to the combination of Human Resources and other resources (Technology / Machinery). This study aims to determine the maximum capacity of services that can be provided in Medical Rehabilitation Poly, General Surgical Poly and Children Poly at Jemursari Islamic Hospital Surabaya. This research is a type of descriptive observational research. The subjects in this study were Medical Rehabilitation Poly, General Surgery Poly and Children’s Poly at Jemursari Surabaya Hospital and the object in this study was the maximum supply in providing services in each poly. There are two data used, primary data and secondary data. Secondary data obtained from secondary data of each poly in RSI Jemursari Surabaya and primary data obtained from interviews through indepth interviews to nurses in Medical Rehabilitation Poly, General Surgery Poly and Children’s Poly. The maximum supply calculation results in  Medical Rehabilitation Poly amounted to 185 patients each day, when compared with the history of poly visit rates of 81%. The results of the maximum supply calculation in General Surgical Poliywere 40 patients each day, when compared with the history of poly visit rates of 112%. The results of the maximum supply calculation in the Children’s Poly were 40 (Room A) dan 80 (Room B) patients each day, when compared to the history of poly visit rates of 125% (Room A) and 62,5% (Room B).